2013
DOI: 10.1097/adm.0b013e318279737b
|View full text |Cite
|
Sign up to set email alerts
|

Self-inflicted Testicular Amputation in First Lysergic Acid Diethylamide Use

Abstract: This report shows that a first and single use of lysergic acid diethylamide in combination with alcohol can cause intoxication with dramatic consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In these cases, the contribution of mental illness to the self-aggressive act is substantial, and one cannot attribute the act exclusively to LSD exposure. Only the case reported by Blacha et al [ 21 ] appears to be of real interest, in that it concerns manual amputation of both testes after first use of LSD in combination with alcohol consumption in a 32-year-old man with no psychiatric history and whose follow-up examination 6 months after the event did not reveal the development of a psychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the contribution of mental illness to the self-aggressive act is substantial, and one cannot attribute the act exclusively to LSD exposure. Only the case reported by Blacha et al [ 21 ] appears to be of real interest, in that it concerns manual amputation of both testes after first use of LSD in combination with alcohol consumption in a 32-year-old man with no psychiatric history and whose follow-up examination 6 months after the event did not reveal the development of a psychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lifetime use of other illicit substances such as marihuana was associated with past-year suicidal thinking and past-month psychological distress, and 97.7% and 97.8%, respectively, of the psychedelic users also reported lifetime marihuana use [88,89]. Furthermore, several case reports describe harmful behavior in particular when psychedelics were consumed together with other psychotropic substances, e.g., alcohol [90][91][92]. An online survey about the single most challenging experience with recreational psilocybin use revealed that 11% put themselves or others at risk of harm, 7.6% sought treatment because of enduring psychological problems, and three cases were associated with the onset of enduring psychotic symptoms [93].…”
Section: Physical and Mental Harm Potentialmentioning
confidence: 99%